Pro- and Anti- Effects of Immunoglobulin A- Producing B Cell in Tumors and Its Triggers - Zhong, Ziwen; Nan, Ke; Weng, Meilin; Yue, Ying; Zhou, Wenchang; Wang, Zhiqiang; Chu, Yiwei; Liu, Ronghua; Miao, Changhong (Frontiers in Immunology, 2021)
B cells are well known as key mediators of humoral immune responses via the production of antibodies. Immunoglobulin A (IgA) is the most abundantly produced antibody isotype and provides the first line of immune protection at mucosal surfaces. However, IgA has long been a divisive molecule with respect to tumor progression. IgA exerts anti- or pro-tumor effect in different tumor types. In this review, we summarize emerging evidence regarding the production and effects of IgA and IgA+ cells in the tumor microenvironment (TME). Moreover, we discuss that the TME cytokines, host diet, microbiome, and metabolites play a pivotal role in controlling the class-switch recombination (CSR) of IgA. The analysis of intratumoral Ig repertoires and determination of metabolites that influence CSR may help establish novel therapeutic targets for the treatment of cancers.